PENGARUH PENGGUNAAN METODE SPEED READING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V UPT SPF SD INPRES BERTINGKAT MAMAJANG II KOTA MAKASSAR - Ewi, Dewi Resky Amalia; Rohana, Rohana; Erma Suryani Sahabuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the effect of using the speed reading method on the reading comprehension ability of fifth-grade students at UPT SPF SD Inpres Bertingkat Mamajang II Makassar City. The study employed a quantitative approach using a quasi-experimental design with the form of Nonequivalent Control Group Design. The population comprised all fifth-grade students at the school, with a purposive sampling technique applied to select 20 students from class V B as the experimental group. Data collection involved administering reading comprehension tests before and after the implementation of the speed reading method. The descriptive analysis showed an improvement in reading comprehension ability after treatment. Inferential analysis using a paired sample t-test indicated a significant difference between the pre-test and post-test scores. The results demonstrate that the speed reading method effectively enhances students' reading comprehension skills.